PENINGKATAN PEMAHAMAN SISWA SEKOLAH MENENGAH KEJURUAN (SMK) MIFTAHUL ULUM KABUPATEN SEMARANG TERHADAP PERAN PEMUDA DALAM PEMBANGUNAN SESUAI UU NO. 40 TAHUN 2009 TENTANG KEPEMUDAAN - Mukharom Mukharom; Dharu Triasih; Endah Pujiastuti (Jurnal Pengabdian kepada Masyarakat, 2020)
Refer to Law No. 40 of 2009 concerning Youth, Article 1 numbers 1-6 that the Youth is an Indonesian citizen entering an important period of growth and development aged 16 (sixteen) to 30 (thirty) years. Youth is a variety of matters relating to the potential, responsibilities, rights, character, capacity, self-actualization, and the ideals of youth. Youth development is the process of facilitating all matters related to youth. Youth services are awareness, empowerment, and development of leadership, entrepreneurship, and youth leadership. Youth awareness is an activity that is directed to understand and respond to environmental changes. Youth empowerment is an activity that awakens the potential and active role of youth. Therefore it is necessary to do community service in the form of understanding of Semarang Miftahul Ulum Vocational School Students about the Role of Youth in Development in accordance with Law No. 40 of 2009 concerning Youth. The problem faced by young people today is that the enormous responsibility in building the nation as the next generation has not yet emerged so that this dedication is important to do, the aim is to give students an understanding that the task is very heavy in filling development in accordance with the Youth Law. The method applied in the implementation of community service by lecturing, question and answer directly and evaluation after the activity is carried out. This service is carried out independently. The implementation was carried out by Semarang University Law Faculty lecturers who are competent in mastering material on youth. Community service was carried out on August 22, 2019 with the concentration of the Youth's Role in Development in accordance with Law No. 40 of 2009 concerning Youth. The result is that almost 80 percent of students do not yet know the legal rules about youth and their responsibilities as youth, and after the delivery of material on youth, they realize that youth have a very big responsibility for the Indonesian state.